2003
DOI: 10.1002/bjs.4345
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of improvement in health-related quality of life in patients undergoing cholecystectomy

Abstract: These data indicate that cholecystectomy is appropriate for patients with symptomatic cholelithiasis and low surgical risk. In terms of HRQoL, the risk to benefit ratio seems poor for patients with asymptomatic gallstones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 25 publications
(15 reference statements)
2
17
0
2
Order By: Relevance
“…Clinical research has shown the detrimental consequences that gallstone disease has on patient’s quality of life [14, 15]. Our hypothesis was that patients who were waiting for an operation, as part of the conservative strategy in the treatment of acute cholecystitis, would have experienced impairment due to recurrent and/or remaining problems from the disease process per se.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical research has shown the detrimental consequences that gallstone disease has on patient’s quality of life [14, 15]. Our hypothesis was that patients who were waiting for an operation, as part of the conservative strategy in the treatment of acute cholecystitis, would have experienced impairment due to recurrent and/or remaining problems from the disease process per se.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical challenge in decision-making is to balance the projected prognosis of expectant management versus the risk, effort, inconvenience and cost of an immediate treatment 'for a particular patient'. By definition, a procedure is considered appropriate if its health benefits exceed its health risks by a sufficiently wide margin, thus making the procedure worth performing [1]. This review will attempt to summarize the information available in the literature regarding the natural history of AsGS in general as well as in special clinical situations, and the risks of cholecystectomy, to put the problem in perspective.…”
Section: Gallbladder Cancer Bile Duct Injurymentioning
confidence: 99%
“…Other studies have found a relationship between unsatisfactory outcome following cholecystectomy and neuropathy, depression or other psychiatric disease based on the quantity of psychiatric medications consumed 13,19,29 . Furthermore, low quality of life has been shown to be associated with persistent pain after cholecystectomy 1,19,30 .…”
Section: Discussionmentioning
confidence: 99%